A new section (Begonia sect. Oligandrae sect. nov.) and a new species (Begonia pentandra sp. nov.) in Begoniaceae from New Guinea - Hughes, Mark; Takeuchi, Wayne (Phytotaxa, 2015)
Begonia pentandra is described from previously unknown environments on the Juha limestone of Papua New Guinea’s Southern Escarpment. It is placed in the newly described Begonia sect. Oligandrae, along with B. brassii, B. chambersiae, B. oligandra and B. sandsiana. The section is endemic to the New Guinea Highlands and is characterised by male flowers with 4–8 stamens and fruits with three, fleshy, horn-like wings.